2013
DOI: 10.3109/13697137.2013.869671
|View full text |Cite
|
Sign up to set email alerts
|

Phytoestrogens induce apoptosis through a mitochondria/caspase pathway in human breast cancer cells

Abstract: These data demonstrate that genistein, resveratrol, and quercetin have antiproliferative effects on breast cancer cells. Their induction of apoptosis involves the activation of both the intrinsic and extrinsic apoptotic pathways, which may be related to the differential affinity to ERα and ERβ. Whether phytoestrogens have similar effects on normal breast cells remains to be examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Our previous studies revealed that the distinctive expression of ER α and ER β may be associated with the apoptotic effects of these phytoestrogens (higher affinities for ER β) and the proliferative effect of E 2 in MCF-7 breast cancer cells (13,14). 8 necessary for proliferation and that ER β opposes the proliferative effects exerted by ER α (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies revealed that the distinctive expression of ER α and ER β may be associated with the apoptotic effects of these phytoestrogens (higher affinities for ER β) and the proliferative effect of E 2 in MCF-7 breast cancer cells (13,14). 8 necessary for proliferation and that ER β opposes the proliferative effects exerted by ER α (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…We then observed both the zymogen and cleaved forms of caspases, including FADD, cytochrome C, tBid, caspase-9, and caspase-3. The decision to use a concentration of 10 −7 M to examine this signaling pathway was based on its effects on cell viability in the present study and in our previous reports (13) and also because of the range of plasma concentrations of phytoestrogens in humans (10nM-10μM) (15). The details of the experiment methods are described as follows.…”
Section: Study Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with those reported by Patisaul et al (49), wherein, ERβ was down-regulated by estrogen in a region specific manner in the rat brain, whereas exposure to coumestrol (phytoestrogen) is thought to modulate ERβ. Chen et al (50) observed the same contrasting pattern between E2 and a group of phytoestrogens (genistein, resveratrol, and quercetin) in the breast cancer cell line MCF-7.…”
Section: Figmentioning
confidence: 78%
“…The structure of quercetin is similar to estrogen, including two hydroxyl groups and a phenol ring [252]. Therefore, quercetin acts as a phytoestrogen that binds to the ER and participates in the regulation of cell growth and gene transcription through estrogen dependent pathway [253, 254] as well as via ER-independent pathway [157]. Quercetin has low bioavailability in humans [255].…”
Section: Natural Products Against Er-positive Breast Cancermentioning
confidence: 99%